Authoritarian Parenting Effect on Children's Executive Control and Individual Alpha Peak Frequency. Issue 4 (23rd August 2021) - Zhang, Jiahe; Yan, Zhixuan; Nan, Wenya; Cai, Dan
ABSTRACT: There is increasing evidence that the authoritarian parenting style has a negative effect on children's executive control, but little is known about the neurobiological mechanism behind this effect, especially the evidence of the resting‐state EEG related to children's brain function. The current study explored the relations between authoritarian parenting and children's executive control among 40 children aged 8–11 years old and examined associations between authoritarian parenting and individual alpha peak frequency (iAPF). Hierarchical regression analysis indicated that after controlling for children's age and parental socioeconomic status, authoritarian parenting style negatively predicts the children's executive control and iAPF in EEG. This study extends previous research on the effect of parenting styles on children's cognitive abilities and provides evidence at the level of neural mechanisms. LAY ABSTRACT: We investigated the influence of authoritarian parenting style on children's executive control and brain activity. The results show that authoritarian parenting style has a negative impact on children's executive control and brain electrical activity in related areas. Research reveals the importance of parenting styles for children's cognitive abilities and brain development.